2012
DOI: 10.1128/jcm.01251-12
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus DNA Splicing in Lebanese Blood Donors and Genotype A to E Strains: Implications for Hepatitis B Virus DNA Quantification and Infectivity

Abstract: Hepatitis B virus (HBV) is one of the major viruses transmissible by blood that causes chronic infection in immunocompromised individuals. The study of 61 HBV carrier blood donors from Lebanon revealed multiple patterns of spliced HBV DNA. HBV DNA splicing was examined and quantified in samples of five genotypes and in seroconversion panels. The Lebanese sample median viral load was 1.5 ×10 2 IU/ml. All strains were genotype D, serotype ayw; 35 clustered as subgenotype D1 and 7 clustere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
(47 reference statements)
3
22
0
1
Order By: Relevance
“…This is consistent with others who reported predominance of D genotype in the studies performed in Arab countries that included females only [13][14][15][16][17][18][19][20][21].…”
Section: Disccussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is consistent with others who reported predominance of D genotype in the studies performed in Arab countries that included females only [13][14][15][16][17][18][19][20][21].…”
Section: Disccussionsupporting
confidence: 81%
“…In Mosul, Iraq, Shafiq [12] [2013] reported that genotype D is the predominant genotype in HBV acute and chronic infections. In addition, another study found that D genotype is the predominant among Mosul blood donors [11].In Arab countries the predominant genotype was D in Saudi Arabia [13], United Arab Emirates [14], Yemen [15], Lebanon [16], Jordan [17], Egypt [25], Libya [18] Mauritania [19], Morocco [20], and Syria [21].…”
Section: Disccussionmentioning
confidence: 99%
“…In a previous study conducted between July 2009 and January 2011, 61 HBsAg positive donors were tested for NAT (35) and when compared to the current study, 21 HBsAg were positive. Both of studies have a comparable distribution of HBV viral load at 2 different periods of time, with a predominance of a low viral load in anti-HBe positive, asymptomatic, blood donors (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…3 Chaar et al previously sequenced 42 HBV full genome strains isolated from Lebanon and demonstrated that genotype D strains were the only circulating viruses; in addition various mutations were found in the S and core genes, those were associated with escape detection or disruption of protein synthesis (35,39,40) In this study, the prevalence of OBI in healthy anti-HBc seropositive blood donors was 0.3% (n = 1/341), only 1 Syrian donor was an OBI carrier with a high anti HBs level > 1000 mIU/mL. Molecular analysis for the detection of any mutation associated with the occult strain was not studied due to plasma volume limitation.…”
Section: Discussionmentioning
confidence: 99%
“…D is the most common genotype among the different settings throughout the previously mentioned Arab states [37][38][39][40][41][42][43][44][45][46].…”
Section: Genotypesmentioning
confidence: 99%